IMPLEMENTATION OF STRATEGIC MANAGEMENT IN POVERTY ALLEVIATION: A CASE STUDY OF DUMAI CITY, RIAU - Prayetno, Prayetno; Irvan, Puji Ananda; Nisyah, Habibah Tun; Rineliana, R.; Tampubolon, Omar Farrakhan (Gapenas Publisher, 2025)
Purpose: This study analyzes the implementation of strategic management in poverty alleviation efforts in Dumai City, Riau, Indonesia. Poverty in Dumai is a multidimensional issue with unique complexities stemming from its status as an international port city and a center for the oil industry. Methodology: Despite a high Gross Regional Domestic Product (GRDP) per capita, Dumai City's poverty rate remains above the average for urban areas in Riau Province, indicating structural inequality in the distribution of economic development benefits. This qualitative research employed a case study method involving in-depth interviews with 25 key informants, observations, Focus Group Discussions (FGDs), and document analysis. Data analysis utilized a SWOT approach to evaluate internal and external factors influencing program success. Findings: The research results demonstrate a positive correlation between strategic management and the effectiveness of poverty alleviation, with strategy formulation identified as the most influential dimension. Dumai City possesses strong leadership commitment, an integrated information system, institutionalized coordination mechanisms, high community participation, and diversified programs. However, weaknesses include limited institutional capacity, suboptimal operational coordination, a dominance of